2022
DOI: 10.1002/job.2678
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the individual‐level conceptualization of dispositional resistance to change: Multilevel effects on the response to organizational change

Abstract: We know much about the factors that determine employees' responses to organizational change. Among these, key factors are those that have to do with employees' personal dispositions and those that have to do with the organizational context. In the present study, we focus on dispositional resistance to change and demonstrate how it can be used at the collective level as a means of characterizing organizations rather than individuals. Specifically, we use it to capture organizations' collective orientation towar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 84 publications
1
12
0
Order By: Relevance
“…First, empirically, many studies (Furst and Cable, 2008; Liu et al. , 2021b; Sverdlik and Oreg, 2022) demonstrated that employee demographics influence employee resistance to change, thus, we included employees' demographic variables (e.g. employee gender, age, educational level and tenure) as control variables.…”
Section: Methodsmentioning
confidence: 99%
“…First, empirically, many studies (Furst and Cable, 2008; Liu et al. , 2021b; Sverdlik and Oreg, 2022) demonstrated that employee demographics influence employee resistance to change, thus, we included employees' demographic variables (e.g. employee gender, age, educational level and tenure) as control variables.…”
Section: Methodsmentioning
confidence: 99%
“…An even more glaring omission is a lack of study of collective performance. Like individual‐level studies, the limited studies of collective reactions have focused on attitudes rather than behavior (e.g., Sverdlik & Oreg, 2022). Given that a common purpose of change initiatives is improved overall performance, and high‐quality change communication is cited one of the most effective methods for proper change implementation, it is striking that the change literature has neglected studies of change communication's effects on collective performance.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…There are multiple variants in compositional modeling (see Chan, 1998), with at its simplest, collective response to change is calculated as a mean of individual responses, which assumes that individual members have the same role in determining the collective response to change. For example, Sverdlik and Oreg (2023) use an additive model as composition approach to justify aggregation of dispositional resistance at the collective level (see also Kanitz et al, 2023) conceptualization of group championing level). Several researchers also focus on the referent‐shift composition models that entail the need for shifting the referent of focal construct before making the aggregation of individual responses to change to represent collective responses to change (e.g., Harvey, 2023; Pallotti et al, 2023; Peng et al, 2023).…”
Section: Coming Together Is Not Just Individual: Delineating Collecti...mentioning
confidence: 99%
“…While there are diverse ways to categorize the collective (e.g., Banerjee, 1992;Macy, 1991;Zerubavel, 2003) This divergence is evident in the papers included in our special issue. Six papers employ a psychology approach (e.g., de Jong et al, 2023;Harvey & Kudesia, 2023;Kanitz et al, 2023;Lam et al, 2023;Peng et al, 2023;Sverdlik & Oreg, 2023). While most of these studies address collective responses to change in a largely agentic manner, it should be noted that many also incorporate theories rooted in social psychology, acknowledging the broader social structure within which the agency operates.…”
Section: Framing Collective Responses To Change Through Agency and St...mentioning
confidence: 99%
See 1 more Smart Citation